539 Frequency related left bundle branch block as cause of chest pain: 'painful LBBB syndrome'. (8th December 2021) - Stronati, Giulia; Torselletti, Lorenzo; Urbinati, Alessia; Ciliberti, Giuseppe; Barbarossa, Alessandro; Principi, Samuele; Silenzi, Marco; Falanga, Umberto; Compagnucci, Paolo; Casella, Michela; Russo, Antonio Dello; Guerra, Federico
Abstract: Aims: A 47-years-old man presented to our cardiology ambulatory due to sudden chest pains, mainly on exertion. His only relevant cardiovascular risk factor was a familiarity for coronaropathy. In 2013 he had undergone a coronary angiography which was negative for stenotic lesions. Since then he was treated with beta-blockers and Ivabradine with mild improvement of the pain. Methods and results: While his previous Holter-ECG reported sinus rhythm [heart rate (HR) 60 b.p.m.] and no alterations of atrioventricular nor of interventricular conduction, his ECG during his examination in our ambulatory showed sinus rhythm (HR 80 b.p.m.), normal atrioventricular conduction but presence of complete left bundle branch block. We therefore performed an ergometric test. His baseline ECG (HR around 65 b.p.m.), at the start of the test, showed no left bundle branch block and the QRS complex was narrow. During the test, at the heart rate of around 85 b.p.m., the ECG showed a complete left bundle branch block. At the same time the patient complained of typical chest pain. The ergometric test was submaximal as it was stopped at the beginning of the third Bruce stage due to the patient's chest pain. No ST segment alterations were found. During the recovery phase, we noted that the left bundle branch block disappeared when the heart rate was below 75 b.p.m. A new coronary angiography was performed and again it showed no stenotic lesion. We therefore concluded our diagnostic workup and diagnosed a frequency related 'painful left bundle branch block syndrome'. Conclusions: 'Painful left bundle branch block syndrome' is defined as the presence of typical chest pain together with left bundle branch block, in the absence of signs of myocardial ischaemia. The pain improves once the conduction defect disappears. The mechanism of the syndrome is not known although it seems to be related to dyssynchrony of the myocardium. It may often be frequency related.